Role of endoplasmic reticulum stress, oxidative stress and inflammation on early aortic vasculopathy of Type 2 Diabetic rat model - Mustapha, Sagir (2022)
Endoplasmic reticulum (ER) stress contributes to other pathological conditions such as insulin resistance, macro- and microvascular complications associated with diabetes. The aim of this study was to elucidate the role of ER stress, endothelial insulin resistance, oxidative stress and inflammation on early vasculopathy in aorta of type 2 diabetic rats (T2DM). The male Sprague-Dawley rats of 8 – 10 weeks old, weighing about 250 to 300 g were employed for this study. The rats were divided into two groups: control group (n=9) and diabetic group (n=18). The diabetic group were placed on high-fat diet (HFD) for 4 weeks. They were then injected intraperitoneally (i.p) with 40 mg/kg of single dose streptozotocin dissolved in 0.1 M sodium citrate buffer of pH 4.5. Rats with fasting blood glucose greater than 11.1 mmol/l were considered to be diabetic. The control rats were on the normal diet and injected with equal volume of sodium citrate. Blood pressure was monitored in a warm, conscious and restrained state using the non- invasive tail-cuff method via a blood pressure monitoring system. At the 13th week, the diabetic rats were randomly divided into two groups: diabetic rats (n= 9) and diabetic rats receiving tauroursodeoxycholic acid (TUDCA) 150 mg/kg/day i.p for two weeks duration (n= 9). At the 15th week, all rats were sacrificed using a mixture of ketamine (300 mg/kg, i.p) and xylazine (30 mg/kg, i.p). After sacrifice, aortas were isolated and mounted on the organ bath to determine acetylcholine- and insulin- mediated relaxations as well as the relaxation mechanisms using pharmacological inhibitors. ER stress marker, regulators and associated relaxation signaling pathways proteins were assessed using Western blotting. In the aorta of control rats, acetylcholine- and insulin-mediated relaxation through activation of eNOS/PI3K, NAD(P)H oxidase and KATP channels pathways. In diabetic rats, acetylcholine- mediated relaxation through activation of eNOS/PI3K and NAD(P)H oxidase pathways, whereas insulin-mediated the relaxation through eNOS/PI3K pathway only. Interestingly, treatment with TUDCA in diabetic rats showed that the relaxation mediated by acetylcholine and insulin were reverted through activation of eNOS/PI3K, NAD(P)H oxidase and KATP channels pathways. The functional study was supported with an enhanced expression of vascular proteins (IRS-1, Akt and eNOS) with corresponding downregulation of ER stress proteins (IRE-1, BiP and PERK) in the diabetic rats receiving TUDCA. Therefore, these data suggested that the inhibition of ER stress could be a potential target for the management of T2DM vasculopathy.